The Effect of a Telephone-Based Self-management Program Led by Nurses on Self-care Behavior, Biological Index for Cardiac Function, and Depression in Ambulatory Heart Failure Patients - Mi Kyoung Moon; JongEun Yim; Mi Yang Jeon (Elsevier, 2018)
Purpose: This study was conducted to examine the effects of a telephone-based self-management support program led by nurses on self-care behavior, biological index for cardiac function, and depression. Methods: This study is a quasi-experiment in nonequivalent control group design. Thirty-eight heart failure patients underwent medical treatment at the hospital (18 heart failure patients in the experimental group and 20 heart failure patients in the control group). The experimental group (n = 18) received the telephone-based self-management support program, which included a 30-minute face-to-face education session and four telephone consultation and education sessions. The face-to-face education session was conducted at the first visit to the outpatient clinic. Thereafter, weekly telephone consultations and education sessions were performed for 4 weeks. Data were analyzed using descriptive statistics, Chi-square test, Fisher's exact test, independent t test, paired t test, and repeated measures analysis of variance using the SPSS/WIN 21.0. Results: The participants in the experimental group showed significantly increased self-care behavior scores (t = 6.65, p < .001), decreased N-terminal pro-brain natriuretic peptide level (U = −2.28, p = .022), improved left ventricular ejection fraction values (t = 2.24, p = .032), and decreased depression scores (t = −3.49, p = .001) compared with the control group. Conclusion: The findings indicate that the telephone-based self-management program is an effective intervention to improve self-management in heart failure patients. Keywords: depression, heart failure, heart function tests, self care, telephone